Epidemic patterns and the immunity levels in hospitalized patients with respiratory syncytial virus infection in 2019-2023 - Linyan Tang; Lanlan Ma; Yan Liang; Xing Chen (Journal of Infection in Developing Countries)
Introduction: The epidemic pattern of the Respiratory syncytial virus (RSV) has changed during the COVID-19 pandemic. To analyze the epidemic pattern of RSV infection and explore the fluctuations of immunity.